A Comparison of Glide Scope Video Laryngoscopy to Direct Laryngoscopy for Nasotracheal Intubation - Khan, Taimur Azam; Shah, Syed Qasim Ali; Beg, Mirza Hamid; Mateen, Osama Abdul; Sharif, Muhammad Huzaifa; Hashmi, Syed Rafat Ali (Pakistan Armed Forces Medical Journal, 2023)
Objective: To compare the ease of intubation using glide scope video laryngoscope versus direct laryngoscopy for nasotracheal intubation.Study Design: Quasi experimental study.Place and Duration of Study: Combined Military Hospital, Rawalpindi Pakistan, Aug 2022 to Feb 2023.Methodology: Patients of either gender with age greater than 18 years with American Society of Anesthesiologists (ASA) Grade I or Grade II planned for elective dental or maxillofacial procedures requiring nasotracheal intubation were included. A total of 60 patients were included, with 30 patients in each group. Recorded variables were time to intubate, glottic grade, use of Magill forceps, first attempt success, failure to intubate and postoperative sore throat.Results: With 60 patients after randomised allocation, 30 were allocated to Group-DL (Direct laryngoscopy) and Group-VL(Video laryngoscopy). The success rate in the first attempt was 27(90%) in Group-DL vs 30 (100%) in Group-VL, and the number of patients who could not be intubated was 1(3.3%) vs 0(0%) in both groups. The glottic grade recorded by the operator under vision, time to intubation, use of Magill forceps and post-operative sore throat in both groups was significant with a p-value of